PERAN ORANG TUA DALAM PENDIDIKAN ANAK USIA DINI MENURUT ISLAM - Masliani; Ahmad Suriansyah; Rizky Amelia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The role of parents in early childhood education is based on Islamic teachings derived from the Qur'an and Hadith, especially regarding the obligation to seek knowledge for every individual. Early childhood education greatly influences the growth of children. The earliest early childhood education teachers are the parents themselves. In Islam, the responsibility and role of parents is not only limited to raising and providing for children. But also caring for, instilling values ​​of faith by teaching monotheism, teaching how to worship, teaching what is Halal and Haram according to Islam, and teaching children to be grateful for Allah's blessings. In addition, parents are also expected to be good role models for children and educate them with love. This paper aims to describe how the responsibility and role of parents in early childhood education, especially early childhood education from an Islamic perspective. This study uses a literature study method whose data sources are relevant and related to the role of parents in early childhood education according to Islam. The results of the study show various good practices in the role of parents in early childhood education according to Islam including instilling the values ​​of monotheism and true aqidah to children, teaching children to pray, teaching children to read the Koran, motivating children to always pray, teaching children to be grateful, motivating children to go to the mosque, teaching children to always maintain their genitals, teaching children to always maintain body cleanliness, teaching children to love each other as fellow creatures of Allah. The purpose of early childhood education is to help the growth and development of children's physical and spiritual so that they are ready to enter further education.